Pharmacopolitics : drug regulation in the United States and Germany - Daemmrich, Arthur A. (Studies in social medicine., 2004)
Advocates of rapid access to medicines and critics fearful of inadequate testing both argue that globalization will result in the easy transfer of pharmaceuticals around the world. In Pharmacopolitics, Arthur Daemmrich challenges their assumptions by comparing drug laws, clinical trials and monitoring systems in the US and Germany.